PROBLEMS OF SELECTION AND EVALUATION OF INNOVATION AND INVESTMENT PROJECTS - Mukhammat U. Baychorov (Вестник Северо-Кавказского федерального университета)
The article analyzes the methods of evaluation of innovation and investment projects and algorithm evaluation and selection of innovation and investment projects. The characteristic criteria in the selection system of innovation and investment projects. Described the effectiveness of innovative-investment project.